2019
DOI: 10.1007/s00404-019-05063-6
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel lymph node mapping using indocyanine green in patients with uterine and cervical neoplasms: restrictions of the method

Abstract: Purpose To establish the surgical, demographic and histopathological factors associated with inaccurate sentinel lymph nodes (SLNs) identification using indocyanine green (ICG) and near-infrared (NIR) fluorescence imaging in uterine and cervical neoplasms during both open and laparoscopic surgery. Methods We reviewed patients with atypical endometrial hyperplasia (AEH), clinical stage I and II cervical cancer or uterine malignancies who underwent primary surgery with SL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 53 publications
1
24
1
3
Order By: Relevance
“…Higher SLN detection rates have been reported to be associated with intra-cervical injection and the use of indocyanine green 7 15. Additionally, patient- and tumor-related factors, including increased body mass index, clinically enlarged lymph nodes, and metastatic lymph nodes, have been associated with decreased bilateral mapping rates 12 13 16 17…”
Section: Discussionmentioning
confidence: 99%
“…Higher SLN detection rates have been reported to be associated with intra-cervical injection and the use of indocyanine green 7 15. Additionally, patient- and tumor-related factors, including increased body mass index, clinically enlarged lymph nodes, and metastatic lymph nodes, have been associated with decreased bilateral mapping rates 12 13 16 17…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a reduction in the factors associated with bilateral detection failure when using an isolated tracer. In the case of Tc-99m, mapping failure by both pre-operative SPECT/CT imaging and intra-operative gamma probe is mainly associated with incorrect tracer injection,14 30 that leads to major venous drainage or peritoneal extravasation. With regard to ICG, incorrect tracer injection is reported less frequently as a cause of mapping failure since the injection can be repeated if necessary.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing concern about the phenomenon of ‘empty node packet’. Bedyńska et al reported that almost 40% of the detection failure with ICG was due to ‘empty packets’ 30. Thomaier et al found that in the first 25 procedures the ‘empty node packet’ rate was 20%, compared with 7% in subsequent procedures 18.…”
Section: Discussionmentioning
confidence: 99%
“…It reported reduced rates of readmission as well as decreased incidence of postoperative complications in the SLND group. In contrast, high grade and non-endometroid EC patients (confirmed on final histology) displayed failure in the mapping process (61) . Overall, SLND has shown promising results in early-stage EC however, better recognition and adoption may aid optimisation of SLN algorithms (3,60) .…”
Section: Role Of Sentinel Lymph Node Dissectionmentioning
confidence: 96%